2005
DOI: 10.1038/sj.ijo.0802947
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of orlistat for the treatment of overweight and obese patients in Ireland

Abstract: Our model suggests that orlistat is effective and cost-effective in obese patients, if after 3 months of treatment, only treatment responders continue treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…Ten studies 26,157,158,[160][161][162][163][167][168][169] used obese cohorts with no comorbidities at baseline. Three studies 164,165,170 presented results for overweight cohorts with T2DM at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies 26,157,158,[160][161][162][163][167][168][169] used obese cohorts with no comorbidities at baseline. Three studies 164,165,170 presented results for overweight cohorts with T2DM at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies 159,168 assumed a linear rate of regain over a 1-year period, based on data from RIO trials that showed a 1-year period to reach baseline weight after re-randomisation to placebo following rimonabant. 115 Four studies 161,163,165,170 modelled a linear regain over a 3-year period, based on a NICE recommendation, 38 whereas one 164 assumed a 5-year period for regain. 175 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept "NNT to gain 1 QALY" was used in a health economic evaluation of orlistat in the treatment of overweight patients (39). No details regarding the calculation of this estimate are given, however, and the study is based on pooled data from 5 RCTs comparing calorie-reduced diet plus orlistat or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear what proportion of this reduction is due to the effects of diet versus medication use but a reduction of this magnitude, if achieved, is sufficient to significantly decrease mortality and the risk of developing cardiovascular disease or cancer [8]. Some studies have shown that anti-obesity medications are a cost-effective form of treatment [9,10], however, the research is often funded by pharmaceutical companies and relies on large assumptions [11]. Despite the potential benefits of using anti-obesity medication a history of safety fears and a variety of side effects may have hampered their use [5,12].…”
Section: Introductionmentioning
confidence: 99%